Predicting the Natural Course of Hemivertebra in Early Childhood: Clinical Significance of Anteroposterior Discordance Based on Three-dimensional Analysis. Issue 23 (1st December 2019) - Chang, Sam Yeol; Nam, Yunjin; Lee, Jeongik; Lee, Na-Kyoung; Chang, Bong-Soon; Lee, Choon-Ki; Kim, Hyoungmin
Abstract : Study Design: A retrospective cohort, radiographic study. Objective: The aim of this study was to compare the progression of scoliosis owing to single hemivertebra (HV) during early childhood, according to the anteroposterior discordance obtained from the three-dimensional computed tomography (3D-CT) studies. Summary of Background Data: Previous studies have utilized 3D-CT for the classification of congenital spinal deformities and have introduced the concept of two types of deformity: unison and discordant anomalies. However, there have been no further studies on the clinical significance of these discordant deformities, especially in the identification of deformities that will progress and require an operation. Methods: We retrospectively analyzed 97 cases of single HV with thoracolumbar scoliosis, diagnosed in children before the age of 3 years and followed up past the age of 6 years. The segmentation of the anterior and posterior components, and anteroposterior discordance of the HV were evaluated using 3D-CT images. Coronal segmental curve angle (SCA) and balance were measured using whole spine plain radiographs. Results: Using 3D-CT, 41 (42.3%) cases of unison HV and 56 (57.7%) discordant HV were identified. Unison HV comprised 21 (21.6%) cases of fully segmented (FS) unison HV and 20 (20.6%) cases of semi-segmented unison HV with corresponding anterior and posterior segmentation. Fifty-six cases of discordant HV were further classified into 4 different types. In the 86 patients who were followed without operation between the ages of 3 and 6 years, the average progression of SCA was significantly larger in FS unison HV (one-way analysis of variance, P  < 0.001). Ten of 86 (11.6%) patients showed a coronal imbalance at the age of 6 years, but the proportion of patients with coronal imbalance was not significantly different among the deformity types. Conclusion: Anteroposterior discordance on 3D analysis is a useful indicator for the progression of congenital scoliosis due to single HV in early childhood. Level of Evidence: 4 Abstract : This study analyzed 97 cases of single hemivertebra with thoracolumbar scoliosis using three-dimesnsional computed tomography. Fifty-six (57.7%) cases had discordant hemivertebra, which were further classified into four different subtypes. The progression of the segmental curve angle between the ages of 3 and 6 years was significantly greater in the fully segmented unison hemivertebra cases.